The Dream - Hunt, Roderick, 2012; Roderick Hunt, 1986; Alex Brychta, 1986 (Oxford reading press UK, 2012)
In "The Dream," Biff has a strange dream where everyday things become very big and confusing. Her teddy bear is giant, and the house is upside down! The story shows how dreams can be silly and surprising. In the end, Biff wakes up and is relieved it was just a dream. This story helps young readers explore imagination and the difference between dreams and reality in a fun, simple way. Let me know if you$1 (Bd like an activity or comprehension questions to go with it!s
The Level 2 Biff, Chip and Kipper Stories provide humorous story lines to engage and motivate children. The popular characters and familiar settings are brought to life by Roderick Hunt and Alex Brychta. The stories are unchanged from the previous edition but the cover notes have been updated to support adults in sharing the story with the child.
H3
Keywords: Supplementary reading material